INVENTORY CONTROL DAN PERENCANAAN PERSEDIAAN BAHAN BAKU PRODUKSI ROTI PADA PABRIK ROTI BOBO PEKANBARU - Puspika, Juliana; Anita, Desi (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2013)
This research was intended to determine the optimal arrangement of rawmaterials’ supply; in this case focusing on the flour items which was based onEconomic Order Quantity method. Also, to prove the effectiveness of this methodin increasing the supply control and flour supply arrangement in Pekanbaru BoboBread Factory. This is a descriptive research. The data collection techniques areinterview, observation, and notes. The analysis method applied is EconomicOrder Quantity (EOQ), Safety Stock, Reorder Point, and Significant Test (t test).The result revealed that using Economic Order Quantity has saved more expensecompared to the current manual calculation used by the factory. Economic OrderQuantity method had saved 67,06% or Rp8.154.569,27 in three years (2010 –2012). Based on the significant test, the t value was 5,77 because t cost is biggerthan t table, so the EOQ method is decent to be applied in Pekanbaru Bobo BreadFactory. It is suggested and recommended to the factory management to considerthe use of EOQ method to minimize the material’s expense and maximize theprofit.Kata Kunci : Inventory Control, Raw Materials’ Supply, and Economic OrderQuantiy Method